Freedom of expression and the media - Amos, Merris; Harrison, Jackie, 1961-; Woods, Lorna (Nijhofff law specials, 2012)
Freedom of expression - particularly freedom of speech - is, in most Western liberal democracies, a well accepted and long established, though contested constitutional right or principle. Whilst based in ethical, rights-based and political theories such as those of: justice, the good life, personal autonomy, self determination, and welfare, as well as arrangements over legitimate government, pluralism and its limits, democracy and the extent and role of the state, there is always a lack of agreement over what precisely freedom of expression entails and how it should be applied. For the purpose.